Pengaruh Good Corporate Governance Terhadap Peringkat Obligasi - Putri Nurmala; Akhmad Sigit Adiwibowo (President University Press, 2021)
Bond ratings are a scale of risk of all bonds traded, which indicates how safe a bond is. The security of a bond is indicated by its ability to pay interest and repay the loan principal. The purpose of this study is to find out empirical evidence that good corporate governance has an effect on bond ratings. This study uses secondary data. The population in this study are non-financial companies listed on the IDX in 2014-2018. The research sample was selected using purposive sampling method. After subtraction with several criteria, as many as 20 companies were set as the sample. The analysis technique in this study uses multiple linear regression analysis. The results of this study indicate that institutional ownership and audit committee have a significant effect on bond ratings. Meanwhile, the independent board of commissioners has no significant effect on bond ratings